Una peculiar visión del derecho. ¿y si por unos minutos nos apartamos de Kant y nos aproximamos a Nietzsche? - Da Giau Roose, Piero (2023)
This work presents reflections on the connection between law and sociology, ethics, morality, religion, literature and philosophy; and links legal concepts— assumed a priori—in their non-philosophical meaning. Raising questions de rived from other branches of human knowledge will allow us to assume and understand the multidisciplinary nature of law, starting from legal situations contrasted with the eminently sociological field. Likewise, we will reflect on religious, moral and ethical issues, in the light of philosophy that questions everything —especially a Nietzschean vision— and from the perspective of literature, which addresses everything.